Gender, Judaism, and Bourgeois Culture in Germany, 1800-1870 - Baader, Benjamin (Indiana University Press, 2006)
In this study of gender and religious culture, Benjamin Maria Baader explores the transformation of Judaism during a period of profound change. In 19th-century Germany, Jews became integrated into the surrounding society, achieved an outstanding degree of upward mobility, embraced bourgeois culture, and adapted Judaism to the modern world. During the same period, women moved from the margins of Jewish society into a more prominent position. Baader examines changes in practices of prayer and synagogue worship, rabbinic writings, the transformation of philanthropic and voluntary organizations, and the new roles assumed by women as educators, activists, and religious writers. By documenting the expansion of women's spaces and women's roles in bourgeois Judaism and tracing the feminization of Jewish men's religious practices, Baader gives fresh insights into the gender organization of traditional Jewish culture and modern German middle-class society.